HEMODYNAMIC AND GAS EXCHANGE RESPONSE IN CHILDREN WITH CNS DISORDERS DURING PROCEDURAL SEDATION UNDERGOING COMPUTED TOMOGRAPHY - R. V. Zhdanov; E. V. Grigoriev (Вестник анестезиологии и реаниматологии)
From the safety point of view, procedural sedation results in fairly frequent complications, typical of the anesthetics being used.The objective: to study the hemodynamics, gas exchange and the character of complications (respiratory disorders, agitation) when using thiopental sodium, ketamine and propofol during procedural sedation in the children with CNS disorders undergoing computed tomography.Subjects and methods. 90 patients at the age from 8 months to 10 years with the risk degree of II–III as per ASA who underwent computed tomography were enrolled in the study. The patients were divided into three groups depending on the anesthetic being used. Changes in hemodynamics, gas exchange and frequency of complications were analyzed.Results. Hypercapnia and reduced saturation were documented in the propofol group, which were the consequences of hypoventilation and they required the respiratory support in the form of oxygen insufflation through the face mask in 46.7% of cases or artificial pulmonary ventilation (30% of cases). In ketamine group, agitation was documented in 6% of cases.Conclusions. For procedural sedation in children with CNS disorders, thiopental sodium is the drug of choice, since it provides the least significant impact on hemodynamics, gas exchange and causes no complications.